TEACHER COMMUNICATION SKILLS - Shamsutinova Nazokatxon; Qodirova Mohlaroyim Ravshanbek qizi (TADQIQOTLAR, 2025)
Annotation:This article explores the significance of teacher communication skills in the educational process. It discusses various forms of communication used by teachers, their impact on student learning, classroom environment, and the development of teacher-student relationships. The article also highlights the key communication competencies every teacher should master, along with challenges and improvement strategies.